The antimicrobial peptide Esc(1-21)-1c increases susceptibility of Pseudomonas aeruginosa to conventional antibiotics by decreasing the expression of the MexAB-OprM efflux pump - Canè, Carolina; Casciaro, Bruno; Di Somma, Angela; Loffredo, Maria Rosa; Puglisi, Elena; Battaglia, Gennaro; Mellini, Marta; Cappiello, Floriana; Rampioni, Giordano; Leoni, Livia; Amoresano, Angela; Duilio, Angela; et al. (Frontiers in Chemistry, 2023)
Introduction: The increase in bacterial strains resistant to conventional antibiotics is an alarming problem for human health and could lead to pandemics in the future. Among bacterial pathogens responsible for a large variety of severe infections there is Pseudomonas aeruginosa. Therefore, there is an urgent need for new molecules with antimicrobial activity or that can act as adjuvants of antibiotics already in use. In this scenario, antimicrobial peptides (AMPs) hold great promise. Recently, we characterized a frog-skin AMP derived from esculentin-1a, namely Esc(1-21)-1c, endowed with antipseudomonal activity without being cytotoxic to human cells. Methods: The combinatorial effect of the peptide and antibiotics was investigated through the checkerboard assay, differential proteomic and transcriptional analysis. Results: Here, we found that Esc(1-21)-1c can synergistically inhibit the growth of P. aeruginosa cells with three different antibiotics, including tetracycline. We therefore investigated the underlying mechanism implemented by the peptide using a differential proteomic approach. The data revealed a significant decrease in the production of three proteins belonging to the MexAB-OprM efflux pump upon treatment with sub-inhibitory concentration of Esc(1-21)-1c. Down-regulation of these proteins was confirmed by transcriptional analysis and direct measurement of their relative levels in bacterial cells by tandem mass spectrometry analysis in multiple reaction monitoring scan mode. Conclusion: These evidences suggest that treatment with Esc(1-21)-1c in combination with antibiotics would increase the intracellular drug content making bacteria more susceptible to the antibiotic. Overall, these results highlight the importance of characterizing new molecules able to synergize with conventional antibiotics, paving the way for the development of alternative therapeutic strategies based on AMP/antibiotic formulations to counteract the emergence of resistant bacterial strains and increase the use of “old” antibiotics in medical practice.